Efeito das condições operacionais do processo de extrusão nas características físicas de snacks de polvilho azedo - Trombini, Fernanda Rossi Moretti [UNESP]; Suman, Priscila Aparecida [UNESP]; Urbano, Luiz Henrique [UNESP]; Leonel, Magali [UNESP]; Mischan, Martha Maria [UNESP] (My University, 2010)
This study aimed to evaluate the effect of extrusion temperature, screw speed and moisture in the production of sour cassava starch snacks on physical characteristics of the product. The process was conducted in a single-screw extruder. The variable parameters were: screw speed (196-264 rpm), temperature in the third zone of the extruder (66 to 134 º C) and moisture of sour starch (15.5 to 22.5%). The extrusion process followed the central composite design for three factors totalizing 20 treatments. The results showed significant effects of temperature, moisture and speed screw on specific volume, expansion ratio, color and texture of products. Under conditions of high temperature and screw speed and low moisture are produced snacks with high expandability and crispy.

Este trabalho teve por objetivo avaliar o efeito da temperatura de extrusão, rotação da rosca e umidade na produção de biscoitos de polvilho azedo, sobre as características físicas do produto. O processo foi conduzido em um extrusor mono-rosca e os parâmetros variáveis do processo foram: rotação da rosca (196 a 264 rpm), temperatura na terceira zona do extrusor (66 a 134ºC) e umidade do polvilho (15,5 a 22,5%). O processo de extrusão seguiu o delineamento central composto rotacional para três fatores totalizando 20 tratamentos. Os resultados obtidos mostraram efeitos significativos da temperatura, rotação e a umidade sobre o volume específico, índice de expansão, cor e textura dos produtos. É possível obter biscoitos de polvilho azedo com melhores características tecnológicas nas condições de elevada temperatura e rotação e baixa umidade, produzindo snacks com elevada expansão, claros e crocantes.
Effect of operational conditions of extrusion process on physical characteristics of sour cassava snacks
Keywords: Starch; Biscuits; Expansion; Color; Texture; Amido; Biscoito; Expansão; Cor; Textura